2016
DOI: 10.1038/srep30726
|View full text |Cite
|
Sign up to set email alerts
|

Natural product derivative BIO promotes recovery after myocardial infarction via unique modulation of the cardiac microenvironment

Abstract: The cardiac microenvironment includes cardiomyocytes, fibroblasts and macrophages, which regulate remodeling after myocardial infarction (MI). Targeting this microenvironment is a novel therapeutic approach for MI. We found that the natural compound derivative, BIO ((2′Z,3′E)-6-Bromoindirubin-3′-oxime) modulated the cardiac microenvironment to exert a therapeutic effect on MI. Using a series of co-culture studies, BIO induced proliferation in cardiomyocytes and inhibited proliferation in cardiac fibroblasts. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
(51 reference statements)
1
31
1
Order By: Relevance
“…Administration of tamoxifen from 3 to 8 days post-MI did not reduce infarct size but improved cardiac function at 8 weeks post-MI and more than doubled the BrdU incorporation in CMs in the border zone (Woulfe et al, 2010). Administration of the GSK3-b-inhibitor BIO to infarcted rats for 2 weeks resulted in reduced ventricular fibrosis and improved cardiac function, but changes in infarct size or stimulation of CM proliferation were not reported in this study (Kim et al, 2016). Recently, Badimon et al (2019) reported a small but significant decrease in infarct size in mice treated with the GSK3 inhibitor SB415286; however, this effect was only observed in an ischemia-reperfusion model and not after permanent coronary ligation (Badimon et al, 2019).…”
Section: Wnt Signalingcontrasting
confidence: 64%
See 1 more Smart Citation
“…Administration of tamoxifen from 3 to 8 days post-MI did not reduce infarct size but improved cardiac function at 8 weeks post-MI and more than doubled the BrdU incorporation in CMs in the border zone (Woulfe et al, 2010). Administration of the GSK3-b-inhibitor BIO to infarcted rats for 2 weeks resulted in reduced ventricular fibrosis and improved cardiac function, but changes in infarct size or stimulation of CM proliferation were not reported in this study (Kim et al, 2016). Recently, Badimon et al (2019) reported a small but significant decrease in infarct size in mice treated with the GSK3 inhibitor SB415286; however, this effect was only observed in an ischemia-reperfusion model and not after permanent coronary ligation (Badimon et al, 2019).…”
Section: Wnt Signalingcontrasting
confidence: 64%
“…Activation of WNT signaling via GSK3-b inhibition with BIO (5 mM) resulted in a 10-fold increase in BrdU incorporation and a 5-fold increase in phosphorylated histone-3-positive cells (Tseng et al, 2006). These results were confirmed by Kim et al (2016), who showed that BIO not only induced BrdU incorporation in cultured neonatal rat CMs but also reduced BrdU incorporation in rat neonatal cardiac fibroblasts. Increased proliferation was also observed in cultured human atrial CMs treated with the GSK3-b inhibitor CHIR99021, albeit that the increase in proliferating CMs was modest (control: 1.83% 6 0.01%; CHIR: 2.67% 6 0.08%); in this study, inhibition of WNT/b-catenin signaling with 4-(1,3,3a,4,7,7a-hexahydro-1,3-dioxo-4,7-methano-2H-isoindol-2-yl)-N-8-quinolinyl-benzamide (IWR-1) resulted in a ∼35% reduction in CM proliferation (Wang et al, 2016).…”
Section: Wnt Signalingmentioning
confidence: 65%
“…When this normal process is not controlled, chronic inflammation leads to functional decline without sufficient repair. A delicate regulation of macrophage phenotype is thus functionally relevant to tissue repair, and we previously showed that chemical-induced macrophage modulation can significantly contribute to cardiac recovery after myocardial infarction (MI) (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The MF-reprogramming approach against cachexia of cardiac origin is supported by preclinical studies demonstrating that M2 polarization (e.g., by EPA) is beneficial for the myocardium, by reducing inflammation and promoting cardiac healing after myocardial infarction (52,111,160,326,341). M2 polarization also counteracts systemic and plaque inflammation in atherosclerotic disorders, thus reducing CHF-associated factors (119,299).…”
Section: E Cachexiamentioning
confidence: 99%